Enhancing English Vocabulary Skill by Integrating Nursery Rhymes English Learning Videos in YouTube into Flipbook Based on Cisaat Local Culture - Nurrahma Restia Fatkhiyati; Atikah Ruslianti; Nurina Azyyati; Tesaannisa (Future Science, 2023)
Enhancing English vocabulary skills is one of the needs of Cisaat preschool children as Cisaat becomes a prominent tourism and educational destination. This initiative aligns with the increasing necessity to uplift English language skills with a digital-oriented approach for students and teachers as well at one of Cisaat’s preschools, Riyadul Jannah. Due to cultivating a more diverse, effective, and an enjoyable learning environment, this community service activity (PKM) aims to impart training in the utilization of YouTube video or audio-visual learning media, seamlessly, integrating a digital teaching materials or digital book (digital flipbook). The method used in this activity is qualitative, by focusing on the students and the teachers as the subject. The data were collected through observation and an interview. The results of the activities indicate that the use of nursery rhymes in YouTube video which integrated with flipbook based on Cisaat local cul-ture, particularly in English vocabulary learning at pre-school, has a posi-tive impact on both teachers and students. For teachers, it raises awareness on the YouTube positive impact and how to apply the flipbook’s material to students based on Cisaat local culture. For students, nursery rhymes offer an effective medium to boost vocabulary skills, motivation, and compre-hension abilities.